UNIT 11.20 Cytometry in Malaria—A Practical Replacement for Microscopy?. Issue 1 (July 2013) - Shapiro, Howard M.; Apte, Simon H.; Chojnowski, Grace M.; Hänscheid, Thomas; Rebelo, Maria; Grimberg, Brian T.
Abstract: Malaria, caused by protozoan Plasmodium parasites, kills ∼800, 000 people each year. Exact figures are uncertain because presumptive diagnoses are often made without identifying parasites in patients' blood either by microscopy, using Giemsa's century‐old stain, or by simpler tests that are ultimately dependent on microscopy for quality control. Microscopy itself relies on trained observers' ability to detect subtle morphological features of parasitized red blood cells, only a few of which may be present on a slide. Quantitative and objective flow cytometric measurements of cellular constituents such as DNA, RNA, and the malaria pigment hemozoin are now useful in research in malaria biology and pharmacology, and can provide more reliable identification of parasite species and developmental stages and better detection of low‐density parasitemia than could microscopy. The same measurements can now be implemented in much smaller, simpler, cheaper imaging cytometers, potentially providing a more accurate and precise diagnostic modality. Curr. Protoc. Cytom. 65:11.20.1‐11.20.23. © 2013 by John Wiley & Sons, Inc.